Antimicrobial activity of wild mushroom extracts against clinical isolates resistant to different antibiotics - Alves, M.J. (2013)
Aims: This work aimed to screen the antimicrobial activity of aqueous methanolic extracts of 13 mushroom species, collected in Braganc¸a, against several clinical isolates obtained in Hospital Center of Tra´s-os-Montes and Alto Douro, Portugal. Methods and Results: Microdilution method was used to determine the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC). MIC results showed that Russula delica and Fistulina hepatica extracts inhibited the growth of gram-negative (Escherichia coli, Morganella morganni and Pasteurella multocida) and gram-positive (Staphylococcus aureus, MRSA, Enterococcus faecalis, Listeria monocytogenes, Streptococcus agalactiae and Streptococcus pyogenes) bacteria. A bactericide effect of both extracts was observed in Past. multocida, Strep. agalactiae and Strep. pyogenes with MBC of 20, 10 and 5 mg ml 1, respectively. Lepista nuda extract exhibited a bactericide effect upon Past. multocida at 5 mg ml 1 and inhibited Proteus mirabilis at 20 mg ml 1. Ramaria botrytis extract showed activity against Enterococcus faecalis and L. monocytogenes, being bactericide for Past. multocida, Strep. agalactiae (MBCs 20 mg ml 1) and Strep. pyogenes (MBC 10 mg ml 1). Leucopaxillus giganteus extract inhibited the growth of E. coli and Pr. mirabilis, being bactericide for Past. multocida, Strep. pyogenes and Strep. agalactiae. Conclusions: Fistulina hepatica, R. botrytis and R. delica are the most promising species as antimicrobial agents. Significance and Impact of the Study: Mushroom extracts could be an alternative as antimicrobials against pathogenic micro-organisms resistant to conventional treatments.